Statistical analysis plan for the PRO B study: open-label, superiority randomised controlled trial of alarm-based patient-reported outcome monitoring in patients with metastatic breast cancer - Pimrapat Gebert; Maria Margarete Karsten; Anna Maria Hage; Adam David Dordevic; Ulrike Grittner (Trials, 2024)
Abstract Background With an increasing collection of patient-reported outcomes (PROs) to measure health-related quality of life (HRQoL) in oncological patients, there is still a lack of standardised strategies on how to interpret and use these data in patient care. Prior research has shown support for the use of digital PRO monitoring together with alarm systems to notify clinicians when the PRO values are deteriorating. This system has demonstrated advantages in improving HRQoL and increasing survival rates among oncology patients. Hence, we designed the PRO B study, a superiority multi-centre randomised controlled trial, to investigate the effects of alarm-based monitoring in metastatic breast cancer patients in Germany. The study protocol for the PRO B study was published in September 2021, and this manuscript describes a formal statistical analysis plan (SAP) for the PRO B study to improve the transparency and quality of this trial. Methods and design The trial aimed to recruit 1000 patients with metastatic breast cancer. However, as of the completion of recruitment on June 15, 2023, we have successfully enrolled 924 patients from 52 breast cancer centres. Patients were 1:1 stratified randomised to the intervention and control groups. App-based PRO questionnaires are sent weekly to the intervention group and every 3 months to the control group. Only patients in the intervention group trigger an alarm if their PRO scores deteriorate, and they are subsequently contacted by the local care team within 48 h. The primary outcome is the fatigue score at 6 months, and secondary outcomes are other HRQoL and overall survival. Evaluation of the superiority of the intervention will be done using a linear mixed model with random intercepts for study centres. Conclusion This detailed SAP defines the main components of the statistical analysis for the PRO B study to assist the statistician and prevent bias in selecting analysis and reporting findings. Version 1 of the SAP was finalised on January 18, 2024. Trial registration DRKS (German Clinical Trials Register) DRKS00024015 . Registered on February 15, 2021.